2018
DOI: 10.22159/ajpcr.2017.v11i1.23410
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Nutraceuticals in Prevention and Treatment of Cancer: A Review

Abstract: The objective of the study was to discuss the preventive and treatment of cancer from flavonoids nutraceuticals from our daily dietary source. There has been increasing interest in the research of flavonoids from dietary sources, due to growing evidence of the versatile health benefits of flavonoids through epidemiological studies. Numerous biological activities have been reported. Some clinical trials or meta-analyses have suggested positive associations between flavonoid intake and human health, Several find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…They are able to induce the apoptosis of cancer cells. These special foods can be used for chemoprevention or as a supportive therapy at treatment of tumor by standard anticancer chemotherapeutics [ 175 , 176 , 177 , 178 , 179 , 180 ].…”
Section: Other Functional Applications Of Human Supplementsmentioning
confidence: 99%
“…They are able to induce the apoptosis of cancer cells. These special foods can be used for chemoprevention or as a supportive therapy at treatment of tumor by standard anticancer chemotherapeutics [ 175 , 176 , 177 , 178 , 179 , 180 ].…”
Section: Other Functional Applications Of Human Supplementsmentioning
confidence: 99%
“…Research findings revealed that flavonoids had been extensively studied in-vitro and in-vivo experiments which give strong support to the anticarcinogenic activity of these compounds 25 . In the present study, two groups of organosulfur compounds and flavonoids present in garlic were subjected to docking studies to understand the binding affinity of them against lung cancer target protein (EGFR).…”
Section: Results and Discussion: Garlicmentioning
confidence: 90%
“…Thus the ability of EAF to inhibit these cell lines suggests that it may have a potential use in breast and leukemic cancers. Several findings for example, have proven that phytoconstituents such as flavonoids have significant anticancer properties [50].…”
Section: Discussionmentioning
confidence: 99%